PERSPECTIVES ON THE SHARIA-COMPLIANT ACCOUNTING PRACTICES IN INDONESIA - Rizal Wira Pamungkas (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This research was carried out with the intention of illuminating, with reference to the Qur'an and Hadith, the theoretical underpinnings as well as the practical applications of accounting in Indonesia. The process of conducting this investigation involved conducting a review of previous research that had been published in a number of books and journals in the same field. The purpose of this research is to investigate the theology behind Islamic accounting, as well as the interpretation of Islamic accounting theory and the accounting procedures used in Indonesia. The Holy Qur'an and the Hadith are both relevant to the subject of this research. According to the findings of this survey, the Hadith and the Qur'an are the primary sources of information for sharia accounting theory. When it comes to applying the theory of sharia accounting, the Maslahah and Maqasid al-Shari'ah scale applies not only to the world but also to other areas. According to the Islamic theoretical framework, Islamic accounting necessitates placing the interests of the group ahead of one's own personal interests. The Islamist account can be conceptually broken down into three different concepts: rahmatan lil' alamin, the spiritual concept, and ukhuwah islamiyah.